2015
DOI: 10.1038/ki.2015.211
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostics identifies risks for graft dysfunction despite borderline histologic changes

Abstract: The significance of borderline changes in kidney allograft biopsies is widely debated. To help resolve this, we studied differences in intrarenal gene expression patterns between early clinical and 3-month protocol biopsies, all of which had borderline histologic changes. The gene expression profiles in training set of patients by microarray analysis and data were validated in a larger cohort using RT-qPCR. There was greater expression of immunity- and inflammation-related genes in the early clinical biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Other published studies of rejection-associated transcripts [40][41][42][43][44][45][46] differ in platforms, histologic classifications, case mix, and organs studied, which complicates direct comparisons. We have related our rejection transcripts to lists of transcripts associated with "acute rejection": Table 2).…”
Section: Comparison To Published Lists Of Acute Rejection-associatementioning
confidence: 99%
See 1 more Smart Citation
“…Other published studies of rejection-associated transcripts [40][41][42][43][44][45][46] differ in platforms, histologic classifications, case mix, and organs studied, which complicates direct comparisons. We have related our rejection transcripts to lists of transcripts associated with "acute rejection": Table 2).…”
Section: Comparison To Published Lists Of Acute Rejection-associatementioning
confidence: 99%
“…Other published studies of rejection-associated transcripts [40][41][42][43][44][45][46] differ in platforms, histologic classifications, case mix, and organs studied, which complicates direct comparisons. We have related our rejection transcripts to lists of transcripts associated with "acute rejection": IFNG-inducible chemokines CXCL10, CXCL11 CXCL9, CXCL10, CXCL11, -IFNG-inducible enzymes, small molecules PLA1A APOL3, BTN3A3, FAM26F,GBP1, GBP2, GBP4, GBP5, IDO1, IRF1, PLA1A, WARS ANKRD22, APOL2, GBP5 43 ; Acute Rejection Transcripts in kidney (ARTs) 48 ; and clinical Acute Rejection (cAR) in kidney.…”
Section: Comparison To Published Lists Of Acute Rejection-associatementioning
confidence: 99%
“…This study showed that the borderline category is usually no rejection, and it can be associated with acute kidney injury and inflammatory primary renal diseases, suggesting that the treatment in these cases should not be focused on renal allograft rejection [43]. In contrast, Hrubá et al observed an increase in immunity and inflammation genes in biopsies for clinical indication with borderline changes performed early in comparison with borderline 3-month protocol biopsies [44]. This increase observed within two weeks of transplantation may be influenced by the initial alloimmune response and by the ischemic injury as well.…”
Section: Transcriptomes In Biopsies Categorized As Borderline Changesmentioning
confidence: 73%
“…Our findings are also consistent with recent gene expression profile microarray data from renal biopsies of patients with BL. Hruba et al [23] observed and validated that donor age and expression of the macrophage receptor C-type lectin domain family 5 member A (CLEC5A) were independent factors of progression in patients with BL. CLEC5A expression is prominent on recruited blood monocytes that enter the tissue upon inflammation and differentiate into proinflammatory cells [24].…”
Section: Discussionmentioning
confidence: 96%
“…After 72 h, flow cytometry evaluation revealed decreased proliferation of CFSElabeled CD8 + and CD4 + T cells cocultured with kidney DCs compared with splenic DCs (*P = 0.02, n = 3 in each group) (e) A 10-fold lower IL-2 levels were observed when CD8 + T cells were cocultured with kidney DCs compared with splenic DCs (n = 2 in each group). examining gene expression profile in patients with BL [23]. Furthermore, the magnitude of the association observed between DeGFR and IL-6 levels is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%